Analysis of Syaria Strategic Management in Facing Business Competition (Study on Mie Gacoan Mayang Jambi City) - Mercyana, Sefi; Mutia, Agustina; Fitri, Sasmita; Yonie, Rika; Harahap, Vinta Deliyani; Rahman, Radiansyah; Usdeldi, Usdeldi (International Journal of Economics (IJEC), 2024)
This research was conducted at Mie Gacoan Mayang, the aim of this research was to determine strategic management in facing business competition. The research carried out was a qualitative descriptive approach. The object of this research is Mie Gacoan Mayang. The data collection techniques used are observation, interviews and documentation, the data collection techniques used are observation, interviews and documentation, the data sources used are primary data and secondary data, and data analysis consists of inductive techniques, deductive techniques and drawing conclusions. The research results obtained regarding Marketing Excellence Strategy Management Analysis, where the marketing excellence strategy is carried out by providing quality products at affordable prices in accordance with the quality of the product in attracting and retaining consumers.